Current Status of Forensic Virtual Autopsy Laboratory Construction in China - Yunle Meng; Tu Lyu; Chaopeng Yang; Guanglong He (Journal of Forensic Science and Medicine)
With the advancements in technology and the evolution of forensic science, virtual autopsy techniques have gained increasing attention and promotion in China. Several provinces have established virtual autopsy laboratories within their public security system. However, these initiatives face challenges including equipment costs, the needs for technological updates, professional training, and the establishment of regulatory standards. This study utilized literature analysis, academic exchanges, surveys, and field investigations to examine the current state of virtual autopsy laboratory construction within the Chinese public security system. It identifies existing issues and explores future prospects when offering recommendations for improvement. The goal is to providing insights that may facilitate the development and enhancement of virtual autopsy laboratories in future.